2009
DOI: 10.1177/0091270008326716
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Desvenlafaxine and Paroxetine on the Pharmacokinetics of the Cytochrome P450 2D6 Substrate Desipramine in Healthy Adults

Abstract: The potential for cytochrome P450 (CYP) 2D6 substrates to interact with desvenlafaxine (administered as desvenlafaxine succinate) and paroxetine was evaluated. In an open-label, crossover study, 20 healthy volunteers (aged 21-50) were randomized to 2 series of 9 days each of desvenlafaxine (100 mg/d) or paroxetine (20 mg/d), separated by a 5-day washout. The CYP2D6 substrate desipramine (50 mg) was administered alone on day 1 and coadministered on day 6 of dosing with either desvenlafaxine or paroxetine. CYP2D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 19 publications
2
16
0
Order By: Relevance
“…80 In vitro data indicate that desvenlafaxine has negligible effect on CYP450 enzymes or on p-glycoprotein activity and, consequently, is believed to have a minimal likelihood of inducing drug interactions. [89][90][91] Gabapentin. Gabapentin is a c-aminobutyric acid analogue indicated for the treatment of partial seizures and postherpetic neuralgia.…”
Section: Pharmacologic Optionsmentioning
confidence: 99%
“…80 In vitro data indicate that desvenlafaxine has negligible effect on CYP450 enzymes or on p-glycoprotein activity and, consequently, is believed to have a minimal likelihood of inducing drug interactions. [89][90][91] Gabapentin. Gabapentin is a c-aminobutyric acid analogue indicated for the treatment of partial seizures and postherpetic neuralgia.…”
Section: Pharmacologic Optionsmentioning
confidence: 99%
“…Phase I hepatic metabolism of desvenlafaxine appears to play a small role in its elimination, marked by metabolism to N,O-didesmethylvenlafaxine by the cytochrome P450 (CYP450) 3A4 pathway [5]. Because desvenlafaxine is primarily metabolized via glucuronidation, and clinical reports have shown that desvenlafaxine exerts minimal effects on the activities of the CYP450 enzymes or p-glycoprotein, the potential ability of other drugs to alter desvenlafaxine metabolism is low [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Paroxetine is a potent inhibitor of CYP2D6, 10,11 the enzyme that plays a major role in the metabolism of metoprolol. 3 This explains why paroxetine increases pharmacokinetic indices of exposure to metoprolol and, hence, the cardiovascular effects of metoprolol.…”
Section: Mechanism Of the Interaction Between Paroxetine And Metoprololmentioning
confidence: 99%
“…It is apparent that most of the commonly used β-blockers are either metabolized by CYP2D6 or eliminated by renal excretion 3,[12][13][14][15][16][17][18][19] ; thus, an awareness of which commonly used antidepressants significantly inhibit CYP2D6 10,11,[20][21][22][23][24][25] will warn clinicians about the risk of a potential drug interaction. Table 3 also lists antidepressants that are mild inhibitors of CYP2D6 10,23,25,26,[29][30][31] ; these are probably associated with lower risk of CYP2D6 drug interactions at usual clinical doses.…”
Section: Other Antidepressants and Other β-Blockersmentioning
confidence: 99%